Effects of Aqueous Extracts from Grape and Grape Seed on Adenosine Deaminase Activity in Cancerous and Non cancerous Human Gastric and Colon Tissues. (2016) - Durak, Zahide Esra; Buber, Suleyman; Ozturk, Bahadır; Kocaoglu, Hilmi
No abstract available